2012
DOI: 10.1016/j.athoracsur.2012.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Etiologies, Risk Factors, and Outcomes After Pericardiectomy

Abstract: Background The leading causes of constrictive pericarditis have changed over time leading to a commensurate change in the indications and complexity of surgical pericardiectomy. We evaluated our single-center experience to define the etiologies, risk factors, and outcomes of pericardiectomy in a modern cohort. Methods We retrospectively reviewed our institutional database for all patients who underwent total or partial pericardiectomy. Demographic, co-morbid, operative, and outcome data were evaluated. Survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
79
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 18 publications
11
79
2
5
Order By: Relevance
“…Long-Term Prognosis After Pericardiectomy are related to the underlying etiology. 4-7, 16 Bertog et al 5 reported that survival at a median follow-up of 6.9 years was 63% among 163 patients undergoing pericardiectomy. Idiopathic CP was related to the best survival (88%), followed by post-CS CP (66%) and post-radiation CP (27%).…”
Section: Discussionmentioning
confidence: 99%
“…Long-Term Prognosis After Pericardiectomy are related to the underlying etiology. 4-7, 16 Bertog et al 5 reported that survival at a median follow-up of 6.9 years was 63% among 163 patients undergoing pericardiectomy. Idiopathic CP was related to the best survival (88%), followed by post-CS CP (66%) and post-radiation CP (27%).…”
Section: Discussionmentioning
confidence: 99%
“…9 Different surgical approaches and techniques, especially median sternotomy versus lateral thoracotomy, partial versus total pericardiectomy, and the need for CPB continue to be debated. 4,6,10,16 Generally, the median sternotomy approach enables a more radical clearance of pericardium overlying the right atrium and venae cavae. 17,18 The left anterolateral thoracotomy approach should be preferred in cases of purulent pericarditis and effusive-constricted pericarditis because of concomitant pyothorax and the risk of sternal infection.…”
Section: Discussionmentioning
confidence: 99%
“…El compromiso pericárdico crónico por LES ha sido comunicado anecdóticamente [1][2][3][4][5] , siendo mucho más frecuente el derrame pericárdico como manifestación de serositis aguda en el contexto de LES activo. No obstante ello, en este caso se llegó a la determinación de LES como unidad diagnóstica etiológica, a partir del estudio de un síndrome edematoso y hallazgo de constricción pericárdica, llamando la atención sobre dicha infrecuente asociación.…”
Section: Discussionunclassified
“…La biopsia pericárdica puede revelar inflamación crónica con predominio de mononucleares, aunque lo más común es fibrosis 18 . La PC por LES es extremadamente infrecuente, existiendo sólo 5 casos publicados desde 1965 [1][2][3][4][5] . El diagnóstico de PC se confirmó con cateterismo cardiaco y las biopsias pericárdicas mostraron fibrosis e inflamación crónica, sin granulomas.…”
Section: Figuraunclassified